Game-Based Learning and Student Motivation in Mathematics - Mohd Ramli, ‘Izzat Syahir; Mistima Maat, Siti; Khalid, Fariza (International Journal of Academic Research in Progressive Education and Development, 2020)
The application of game-based learning (GBL) is seen to have many benefits in helping to improve the quality of the teaching and learning process. GBL approach will encourage students to solve problems and self-learning and thus enable students to learn a mathematical concept without realizing it. The review findings show that GBL helps teachers to motivate student engagement in Mathematics. This is because GBL is regarded as a potential means for improving students' confidence and increasing their motivation by incorporating challenge, curiosity and fantasy to a specific problem. The application of GBL has a positive impact on student motivation and involvement in Mathematics learning. Further reading should be made on the motivational impact of student self-efficacy. This is because previous studies have also found that student motivation influences students' self-efficacy in that students who believe in their own abilities are more motivated to engage in learning